(untitled) (ResearchJet Journal of Analysis and Inventions, 2021)
Sinusitis is an inflammation of the mucous membrane of the paranasal sinuses, which is caused by viruses, bacteria, fungi or allergic processes. Symptoms of sinusitis often include nasal congestion, purulent discharge from the nasal cavity, facial pain in the area of projection of the paranasal sinuses, weakness, headache, and high fever.